Studies on the civilization of Islam - Gibb, H. A. R. (Hamilton Alexander Rosskeen) Sir 1895-1971 (Princeton legacy library, 1962)
Ranging from studies on Sufism and the Koran to discussion of nineteenth and twentieth-century Arabic literature, these essays on the law and literature of Islamic society illustrate the unique vision of one of the world's great Orientalists.